Calathiscus tantillus, a new genus and new species of scleractinian coral (Scleractinia, Poritidae) from the Gulf of Oman - Claereboudt, Michel R.; Al-Amri, Issa S. (Zootaxa, 2004)
Calathiscus tantillus new genus & new species (Scleractinia, Poritidae) is described from several specimens collected along the north coast of the Sultanate of Oman and Masirah Island. The zooxanthellate genus has a massive growth form, although colonies remain very small (< 40 mm). The skeletal characteristics are intermediate between Porites and Goniopora, with calices averaging 1.7 mm in diameter. The polyps, fully extended during the day in most specimens, have a long tubular column topped by a wide conical oral disc surrounded by 15 22 tentacles. The characteristics of this new species and genus are discussed in relation to other genera in the family: Porites, Goniopora, Stylarea, Alveopora and Poritipora.